Analisis Determinan Penerimaan Pajak Hotel dan Restoran - Sahara Sanitra; Syapsan Syapsan; Dahlan Tampubolon (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The purpose of this study is to examine the impact of the number of hotel rooms, restaurants, tourist visits, and GDP on hotel and restaurant tax revenues in Kuantan Singingi Regency, as well as to determine which variables have the most impact on hotel and restaurant tax revenues. From 2010 to 2020, the researchers employed a quantitative research design with time series data from the Regional Revenues and Expenditures Budget (APBD) and the Kuantan Singingi Regency's Central Statistics Agency (BPS). The multiple linear regression model is used to determine whether the independent variable has a significant effect on the dependent variable. The findings revealed that the number of hotel rooms and restaurants in Kuantan Singingi Regency had no significant impact on hotel and restaurant tax collections. In Kuantan Singingi Regency, the amount of tourist visits and GDP have a substantial impact on hotel and restaurant tax collections. The amount of tourist visits and GDP have the greatest impact on hotel and restaurant tax revenues in Kuantan Singingi Regency from 2010 to 2020.